Disparities in the Crime of Petty Theft and Aggravated Theft: Study of the Supreme Court of the Republic of Indonesia Regulation Number 2 of 2012 - Bukit, Efraim Abigail; Ismaidar, Ismaidar; Siregar, Mhd Azhali (JURNAL SYNTAX IMPERATIF : Jurnal Ilmu Sosial dan Pendidikan, 2025)
This research aims to discuss in depth the analysis of legal regulations and disparities in the crime of theft, as well as analyze the obstacles and policies in law enforcement of the crime of theft. The type of research used is normative juridical with a descriptive-analytical approach, discussing existing legal symptoms and problems and testing them based on laws regulations, and legal norms. The results of this study show that the crime of theft is classified into ordinary theft under Article 362, theft under Article 363, petty theft under Article 364, and Theft with violence under Article 365. The cause of disparities in theft crimes is caused by conflicting criminal rules, judges' considerations, and the integrity of law enforcement. Obstacles and policies for law enforcement of theft include: limits on the value of goods, lack of reports and victim participation, limited resources, and technical and procedural obstacles. To overcome these obstacles, legal policies are needed such as: improving the quality and quantity of law enforcement officials, implementing restorative justice, and making repressive and preventive efforts to anticipate crime.